Cases of pN1b and pM1 Papillary Microcarcinoma of the Thyroid - Takebayashi, Shinji; Shinohara, Shogo; Mizuno, Keisuke; Saida, Koji; Hayashi, Kazuki; Yamamoto, Ryosuke; Michida, Tetsuhiko; Kikuchi, Masahiro; Fujiwara, Keizo; Naito, Yasushi (International Journal of Practical Otolaryngology, 2018)
Introduction Papillary thyroid carcinoma has a relatively good prognosis among malignant tumors of the thyroid. Therefore, a “wait and see” strategy is often adopted for patients with micropapillary thyroid carcinoma. On the other hand, patients with papillary thyroid carcinoma with N1b or M1 disease are known to show a poor prognosis. Here, we investigated the differences in the characteristics between patients with papillary thyroid microcarcinoma with and without N1b metastatic nodes/distant metastases to identify the risk factors for metastasis.Methods The retrospective study was performed in patients with thyroid microcarcinoma who were treated at the Kobe City Medical Center General Hospital from 2007 to 2017. The characteristics of the patients with thyroid microcarcinoma who were classified as having N1b or M1 disease (N1b/M1 group) were compared with those of patients with the same cancer classified as having N0, N1a, or M0 disease (N0/N1a group).Results A total of 65 patients were enrolled in this study; 12 were classified into the N1b/M1 group and 53 were classified into the N0/N1a group. The proportion of males was significantly higher in the N1b/M1 group than in the N0/N1a group. There were no statistically significant differences in the distribution of the tumor sites, the ultrasonographic findings, or the frequency of the presence of multiple carcinomas. Although three patients died due to other causes, there were no patients who died due to papillary thyroid carcinoma.Conclusion No significant predictors were identified for classifying patients with papillary thyroid microcarcinoma into the N1b/M1 group in this study. However, our findings suggested that male patients with papillary thyroid microcarcinoma require more careful follow-up in comparison to female patients with this cancer.
Keywords: thyroid microcarcinoma; papillary carcinoma; metastasis; male patients; risk factor